Women's health, hormonal balance, and personal autonomy - Segarra, Ignacio; Menárguez, Micaela; Roqué, María Victoria (Frontiers in Medicine, 2023)
Hormone-based contraception disrupts hormonal balance, creating artificial states of anovulation and threatening women's health. We reviewed its main adverse effects and mechanisms on accelerated ovarian aging, mental health (emotional disruptions, depression, and suicide), sexuality (reduced libido), cardiovascular (brain stroke, myocardial infarction, hypertension, and thrombosis), and oncological (breast, cervical, and endometrial cancers). Other “collateral damage” includes negative effects on communication, scientific mistrust, poor physician–patient relationships, increased patient burden, economic drain on the healthcare system, and environmental pollution. Hormone-sensitive tumors present a dilemma owing to their potential dual effects: preventing some cancers vs. higher risk for others remains controversial, with denial or dismissal as non-relevant adverse effects, information avoidance, and modification of scientific criteria. This lack of clinical assessment poses challenges to women's health and their right to autonomy. Overcoming these challenges requires an anthropological integration of sexuality, as the focus on genital bodily union alone fails to encompass the intimate relational expression of individuals, complete sexual satisfaction, and the intertwined feelings of trust, safety, tenderness, and endorsement of women's femininity.